2000
DOI: 10.1002/(sici)1520-6300(200005/06)12:3<363::aid-ajhb6>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of maximum increment age in height and weight during adolescence and the effect of World War II

Abstract: An attempt was made to estimate the maximum increment age (MIA) in height and weight of Japanese boys and girls during the birth years 1893–1990 through the published data of the Ministry of Education, Science, Sports and Culture in Japan. In cases where the same maximum annual increment occurred in two or three successive age classes in a birth year cohort, a new formula (see Eq. 2) was developed to estimate the MIA. The existing formula for estimating MIA was modified to remove the mathematical deficiency (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The increases in height over the years in certain populations have been found to be mainly due to the increase in leg length and not due to an increase in trunk length [9,10]. In a Norwegian study [11], only 20% of the secular increase in height in the period 1921-1962 was related to sitting height, while for Japanese children the effect of the secular trend from 1957 to 1977 was completely due to increased leg length [12,13]. In addition to a significant trend towards greater relative long-leggedness, Ali et al demonstrated earlier spurt in leg length compared to spurt in total height in post-war Japan [14].…”
Section: Discussionmentioning
confidence: 99%
“…The increases in height over the years in certain populations have been found to be mainly due to the increase in leg length and not due to an increase in trunk length [9,10]. In a Norwegian study [11], only 20% of the secular increase in height in the period 1921-1962 was related to sitting height, while for Japanese children the effect of the secular trend from 1957 to 1977 was completely due to increased leg length [12,13]. In addition to a significant trend towards greater relative long-leggedness, Ali et al demonstrated earlier spurt in leg length compared to spurt in total height in post-war Japan [14].…”
Section: Discussionmentioning
confidence: 99%
“…Significant secular increases in stature and decreases in the estimated ages at maximum increment in Asian children (The definition of maximum increment (I max ) age and age at PHV is roughly the same; how-ever, maximum increment age is estimated from observed data, while age at PHV is estimated from fitted data) have also been reported by various authors (Matsumoto, 1982;Ohsawa and Ji, 1993;Ji C-Y et al, 1995;Ali and Ohtsuki, 2000). Matsumoto (1982) found a cohort of Japanese boys in 1936 had an I max in height at age 15 years whereas the 1960 cohort had an I max at age 13 years, a decrease of 2.0 years in 24 years.…”
Section: Secular Change In Age At Phvmentioning
confidence: 69%
“…Since movement of Japanese boys and girls in and out of Japan is relatively insignificant, cross-sectional data can be converted into birth-year cohorts (Matsumoto, 1982;Ali and Ohtsuki, 2000). For example, the birth-year cohort born in 1893 reached six years of age (6.00-6.99 years) on the 2nd of April in 1900; seven years of age (7.00-7.99 years) at the 2nd of April in 1901, and so on.…”
Section: Cohort Datamentioning
confidence: 99%